Bronisław Ferdynand Trentowski vs. panslawizm rosyjski: Bronisław Ferdynand Trentowski vs. Russian Pan-Slavism - Starzyńska-Kościuszko, Ewa (Przegląd Wschodnioeuropejski, 2021)
In the article I recreate and analyze the attitude of Bronisław Ferdynand Trentowski (1808-1869), one of the leading Polish representatives of “national philosophy”, participant of November Uprising and political emigrant, towards Russian Pan-Slavism. In opposition to Pan-Slavism, Trentowski introduced the idea of the Slavic Reich. Originally he based it on values specific to Western culture (occidentalism), and later on the conservative-catholic idea of Poland as the “Christ of Nations”. Combination of these two doctrines (Russian pan-Slavism and Polish messianism) offers an insight into historical premises of Polish and Russian national identities. The reconstruction of Trentowski’s position is proceeded by synthetic characteristics of Slavophilia and Pan-Slavism in Russia.